Development Integrating Augmented Reality, Artificial Intelligence, and Graphic Design to Enhance Learning Quality in Higher Education - Yolandita Angga Reza (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study developed and evaluated interactive learning media integrating augmented reality (AR), artificial intelligence (AI), and graphic design principles for higher education. Using a Design-Based Research approach, the media were iteratively designed, implemented, and refined with undergraduate graphic design students at Universitas Sains Indonesia. Learning effectiveness was assessed through pre- and post-tests, engagement measures, user-experience evaluation, observations, and interviews. Results showed significant improvement in learning outcomes, with a moderate normalised gain (N-Gain = 0.60), a large effect size (Cohen’s d = 0.85), and a significant difference between pre- and post-test scores (p < 0.001). Students also reported high engagement and positive user experience. Qualitative findings indicated that AR supported immersive conceptual visualisation, while AI enabled adaptive feedback and personalised learning. The findings suggest that combining AR, AI, and graphic design can create an interactive, adaptive, and visually effective learning environment that enhances learning outcomes and student engagement.